Direct energy gap of Sb2Te3 synthesised by solid-state microwave plasma - Suriwong T. (2014)
The usefulness of microwave heating and microwave generation of plasma for solid-state synthesis of Sb2Te3 crystals is reported. Lengths of time and molar ratios of Sb:Te were varied to achieve pure products heated by a 900 W microwave-irradiated plasma. In the present research, the products were Sb2Te3 with a rhombohedral crystal system using 2:2, 2:1.75 and 2:1.5 molar ratios of Sb:Te, and lengths of time of 10 and 20 min. Their different crystallographic planes were also detected, including four Raman shifts at 93.9, 102.6, 139.2 and 263.7 cm-1, and direct energy gaps (Eg) in a range of 0.340-0.515 eV. © 2011 The Institution of Engineering and Technology.